Electrochemical device and electric appliance comprising same

By adding an appropriate amount of fluorovinyl carbonate to the electrolyte of the lithium battery and controlling the ratio of its content to the unit reaction area of ​​the positive electrode active material, the manganese dissolution problem caused by high content of manganese positive electrode active material is solved, and the circulation and storage performance of the lithium battery is significantly improved.

CN119905664AActive Publication Date: 2025-04-29NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510145156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-04-29
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

When existing lithium batteries use positive electrode active materials with high content of manganese, manganese elements are prone to dissolution, resulting in the destruction of the negative electrode interface protective film layer, which in turn affects the circulation and storage performance of lithium batteries.

Method used

By adding an appropriate amount of fluorovinyl carbonate to the electrolyte and controlling the ratio of its content to the unit reaction area of ​​the positive electrode active material within a specific range, a protective layer is formed to reduce manganese dissolution and a stable protective layer is formed at the negative electrode.

Benefits of technology

The circulation and storage performance of lithium batteries are significantly improved, ensuring the performance requirements of high-manganese content positive electrode materials in the battery, while reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005266222450000141
    Figure BDA0005266222450000141
  • Figure BDA0005266222450000151
    Figure BDA0005266222450000151
  • Figure BDA0005266222450000152
    Figure BDA0005266222450000152
Patent Text Reader

Abstract

The invention relates to an electrochemical device which comprises a positive electrode, a negative electrode, an isolating membrane and an electrolyte, the electrolyte comprises fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01%-5% based on the mass of the electrolyte; the positive electrode comprises a positive electrode active material, the positive electrode active material comprises an Mn element, and the content of the Mn element is greater than or equal to 15% based on the mass of the positive electrode active material; the unit reaction area of the positive electrode active material is c, and a and c meet the following relation in terms of m < 2 > / cm < 2 >: a / c is more than or equal to 0.0006 and less than or equal to 6.25; wherein the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material. The electrochemical device provided by the invention ensures the performance requirements of the battery after the content of the manganese element in the positive electrode material is improved, so that the cost and the performance of the battery product are both considered.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application date of March 31, 2022, application number 202210335359.9, and invention name “An electrochemical device and an electrical appliance comprising the same”. Technical Field

[0002] The present application relates to the field of energy storage technology, and more specifically to an electrochemical device and an electrical appliance comprising the same. Background Art

[0003] At present, the concepts of carbon neutrality and carbon peak have accelerated the development of the new energy industry, and lithium batteries are an important part of the new energy industry. With the continuous expansion of demand for lithium batteries, the demand for raw materials of transition metal elements such as cobalt, nickel, and manganese is also increasing accordingly, which has caused the prices of cobalt and nickel related resources to rise. Therefore, the industry has been seeking to reduce costs by increasing the content of manganese (Mn) in the positive electrode materials. However, the high content of manganese in the positive electrode active material is prone to dissolution problems. The dissolved manganese is deposited on the negative electrode, causing the destruction of the negative electrode interface protective film layer (SEI (solid electrolyte interphase)), resulting in poor cycling performance and storage performance of lithium batteries. Summary of the invention

[0004] The present application is made in view of the problems existing in the above-mentioned prior art, and its purpose is to provide an electrochemical device and an electrical appliance containing the same to solve the above-mentioned problems, that is, to eliminate or at least alleviate the problems of poor cycling performance and storage performance of lithium batteries caused by using a high content of manganese in the positive electrode active material.

[0005] In order to achieve the above objectives, the present application provides an electrochemical device and an electrical appliance comprising the same.

[0006] In one aspect, the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein

[0007] The electrolyte includes fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5%, based on the mass of the electrolyte;

[0008] The positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and a content of the Mn element is greater than or equal to 15%, based on the mass of the positive electrode active material;

[0009] The unit reaction area of ​​the positive electrode active material is c, expressed in m 2 / cm 2 a and c satisfy the following relationship: 0.0006≤a / c≤6.25; wherein the unit reaction area is the unit area (cm 2) of the positive electrode active material weight W (g) and the specific surface area BET (m 2 / g).

[0010] In any embodiment, the electrochemical device satisfies at least one of the following conditions:

[0011] 0.0006≤a / c≤2.5;

[0012] The content of the fluoroethylene carbonate is 0.05% to 5%, based on the mass of the electrolyte;

[0013] The range of W is 8 mg / cm 2 Up to 35mg / cm 2 , the range of BET is 1m 2 / g to 5m 2 / g.

[0014] In any embodiment, the Dv10 / Dv99 of the positive electrode active material is z, and a / z is 0.01 to 1.

[0015] In any embodiment, the electrolyte further includes vinylene carbonate (VC), and the content b of the vinylene carbonate is 0.01% to 5%, based on the mass of the electrolyte.

[0016] In any embodiment, b and a satisfy the following relationship: 0.11a-0.05% <b<5.1a+0.45%。

[0017] In any embodiment, in the positive electrode active material, the content of Mn element is x, b / x≥10 -3 .

[0018] In any embodiment, the electrolyte further includes an additive A, and the additive A is selected from at least one of methylene methanedisulfonate (MMDS), 1,3-propylene sultone (PES), 1,3-propane sultone (PS), succinic anhydride (SA), lithium difluorophosphate (LiPO2F2), 2-fluoropyridine (2-PY) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0019] In any embodiment, the content of the additive A is 0.01 to 10%, based on the mass of the electrolyte.

[0020] In any embodiment, the electrolyte further contains dimethyl carbonate (DMC), and the content of the dimethyl carbonate is less than or equal to 5%, based on the mass of the electrolyte.

[0021] In any embodiment, the positive electrode active material includes at least one of lithium manganese oxide and lithium nickel cobalt manganese oxide.

[0022] In any embodiment, the electrochemical device satisfies at least one of the following conditions:

[0023] The content of the fluoroethylene carbonate is 0.05% to 3%, based on the mass of the electrolyte;

[0024] The range of W is 13 mg / cm 2 Up to 30mg / cm 2 , the range of BET is 1.2m 2 / g to 3.5m 2 / g;

[0025] The electrolyte further comprises vinylene carbonate (VC), wherein the content of the vinylene carbonate is 0.01% to 2%, based on the mass of the electrolyte;

[0026] The electrolyte further comprises dimethyl carbonate, wherein the content of the dimethyl carbonate is less than or equal to 1%, based on the mass of the electrolyte;

[0027] The content of Mn element in the positive electrode active material is less than or equal to 60%;

[0028] The positive electrode active material has a Dv10 / Dv99 of z and a / z of 0.05 to 0.3.

[0029] On the other hand, the present application also provides an electrical appliance comprising the electrochemical device.

[0030] It was unexpectedly found that, when the manganese content in the positive electrode active material is increased, the cycle performance and storage performance of the battery can be significantly improved by controlling the ratio of the fluoroethylene carbonate content in the electrolyte to the unit reaction area of ​​the positive electrode active material within the range of the present invention. This ensures the performance requirements of the battery after the manganese content in the positive electrode material is increased, thereby achieving a balance between the cost and performance of the battery product. DETAILED DESCRIPTION

[0031] In the following, the detailed description specifically discloses the embodiments of the electrochemical device and its manufacturing method, positive and negative electrode plates, electrolyte and electrical appliances of the present invention. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0032] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0033] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0034] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0036] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0037] The terms "above" and "below" used in this application include the number, for example, "one or more" means one or more, and "one or more of A and B" means "A", "B" or "A and B".

[0038] The term "at least one" as used in this application means one or more, for example, "at least one of A, B or C" means "A", "B", "C", "A and B", "A and C", "B and C" or "A, B and C".

[0039] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0040] Fluoroethylene carbonate, also known as 4-fluoro-1,3-dioxolan-2-one.

[0041] Unless otherwise stated, contents and percentages throughout this application are based on weight.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0043] Since the high content of manganese in the positive electrode active material is prone to dissolution, the dissolved manganese is deposited on the negative electrode, causing the destruction of the negative electrode interface protective film (SEI), thereby resulting in poor cycle performance and storage performance of the lithium battery. After a large number of experiments, the inventors found that when the electrochemical device of the present invention is used, the above problems can be significantly improved.

[0044] Therefore, the first aspect of the present application provides an electrochemical device, which includes a positive electrode, a negative electrode, a separator and an electrolyte, wherein

[0045] The electrolyte includes fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5%, based on the mass of the electrolyte;

[0046] The positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and the content x of the Mn element is greater than or equal to 15%, preferably greater than or equal to 25%, further preferably greater than or equal to 30%, preferably less than or equal to 60%, based on the mass of the positive electrode active material;

[0047] The unit reaction area of ​​the positive electrode active material is c, expressed in m 2 / cm 2 a and c satisfy the following relationship: 0.0006≤a / c≤6.25; wherein the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material.

[0048] Without being limited to any theory, the inventor believes that fluoroethylene carbonate (FEC) can be oxidatively decomposed on the positive electrode surface and form a protective layer with the lithium salt in the electrolyte on the positive electrode surface, reducing manganese dissolution, and can also form a stable protective layer on the negative electrode, reducing the damage caused by the reduction of manganese dissolved from the positive electrode in the negative electrode. However, FEC itself has poor thermal stability and sometimes decomposes to produce HF, which accelerates the dissolution of manganese in the positive electrode. After research, the inventor found that when a high content of manganese is used in the positive electrode active material, the ratio of the content of FEC (a, based on the mass of the electrolyte) to the unit reaction area of ​​the positive electrode active material (c, which is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material) is controlled within the scope of the present invention, which can fully guarantee the protective effect of FEC in the positive and negative electrode film formation, while also reducing the adverse effects of decomposition of excessively high content.

[0049] Electrolyte

[0050] The electrolyte plays a role in conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte includes electrolyte lithium salt and solvent.

[0051] In some embodiments, the electrolyte lithium salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, lithium aluminate, lithium tetrachloroaluminate, lithium chloride, lithium fluoride, lithium perfluorobutylsulfonate and lithium tetrafluorooxalatophosphate.

[0052] In some embodiments, the content of the electrolyte lithium salt may be 1 mass % to 30 mass %, preferably 5 mass % to 20 mass %, preferably 8 mass % to 15 mass %, based on the mass of the electrolyte.

[0053] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dioxolane, dimethyl ether, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0054] In some embodiments, the content of the solvent may be 20% by mass or more, preferably 30% by mass or more, further preferably 40% by mass or more, further preferably 50% by mass or more, further preferably 60% by mass or more, based on the mass of the electrolyte.

[0055] In some embodiments, the electrolyte includes fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5%, preferably 0.05% to 3%, more preferably 0.05% to 2%, based on the mass of the electrolyte.

[0056] In some embodiments, the electrolyte further comprises vinylene carbonate (VC), and the content b of the vinylene carbonate is 0.01% to 5%, preferably 0.01% to 4%, and further preferably 0.01% to 2%, based on the mass of the electrolyte.

[0057] In some embodiments, b and a satisfy the following relationship: 0.11a-0.05% <b<5.1a+0.45%。

[0058] In some embodiments, the electrolyte further includes an additive A, wherein the additive A is selected from at least one of methylene methanedisulfonate (MMDS), 1,3-propylene sultone (PES), 1,3-propane sultone (PS), succinic anhydride (SA), lithium difluorophosphate (LiPO2F2), 2-fluoropyridine (2-PY) or lithium bis(fluorosulfonyl)imide (LiFSI).

[0059] In some embodiments, the additive A is selected from at least one of 1,3-propane sultone and 2-fluoropyridine.

[0060] The content of the additive A is 0.01% to 10%, preferably 0.01% to 6%, based on the mass of the electrolyte.

[0061] In some embodiments, the electrolyte further contains dimethyl carbonate (DMC), and the content of the dimethyl carbonate is less than or equal to 5%, based on the mass of the electrolyte.

[0062] In some embodiments, the content of dimethyl carbonate is less than or equal to 1%, based on the mass of the electrolyte.

[0063] In some embodiments, the electrolyte further includes other additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0064] positive electrode

[0065] In the present application, the positive electrode is a positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0066] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0067] The positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a Mn element, and the content x of the Mn element is 15% to 60%, based on the mass of the positive electrode active material; the unit reaction area of ​​the positive electrode active material is c, measured in m 2 / cm 2 a and c satisfy the following relationship: 0.0006≤a / c≤6.25, preferably 0.001≤a / c≤4.5, more preferably 0.001≤a / c≤2.5; wherein the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material.

[0068] In some embodiments, W is in the range of 8 mg / cm 2 Up to 35mg / cm 2 , the range of BET is 1m 2 / g to 5m 2 / g. More preferably, the range of W is 13 mg / cm 2 Up to 30mg / cm 2 , the range of BET is 1.2m 2 / g to 3.5m 2 / g.

[0069] In some embodiments, b / x ≥ 10 -3 , preferably b / x≤0.1, wherein b is the content of vinylene carbonate, and x is the content of Mn element.

[0070] In some embodiments, x and a satisfy x×e a The value of is from 0.1 to 1.2, preferably from 0.15 to 0.7, where e is the base of the natural logarithm.

[0071] In the present application, the specific surface area BET is tested by the nitrogen adsorption method (GB / T19587-2017). For example, the sample is baked in a vacuum oven at 120°C for 2 hours before testing; the six-point BET method (i.e., P / P0=0.05 / 0.10 / 0.15 / 0.2 / 0.25 / 0.3) is used for testing; the nitrogen purity used is 99.999% and the liquid nitrogen temperature is -196°C.

[0072] The weight W of the positive electrode active material layer per unit area is determined by the following method: take a positive electrode sheet with a certain area S and a positive electrode active material layer on both surfaces of the current collector, scrape the positive electrode active material layer off the positive electrode current collector (scrape off the material except the current collector), weigh the weight m of the powder, and the weight per unit area W = m / (S×2); or

[0073] Take a positive electrode with a certain area S1 and an active material layer on one surface of the current collector, scrape the positive electrode active material layer from the positive electrode current collector (scrape off all materials except the current collector), weigh the weight m1 of the powder, and the weight per unit area W = m1 / S1.

[0074] Then the weight W (g / cm 2 ) multiplied by the specific surface area BET (m 2 / g), and the unit reaction area c (m 2 / cm 2 ).

[0075] In some embodiments, the positive electrode active material may also include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0076] In some embodiments, the content of the positive electrode active material in the positive electrode film layer is not less than 80 weight%, optionally not less than 90 weight%, and further preferably not less than 95 weight%, based on the total weight of the positive electrode film layer.

[0077] In some embodiments, the Dv99 of the positive electrode active material is y μm, and y ranges from 20 to 60, preferably 25 to 55, and more preferably 30 to 53.

[0078] In the present application, when the particles of the positive electrode active material are too small, the reaction contact area is large and there are many side reactions, while when the particles of the positive electrode active material are too large, the ion transport path inside the particles is long, affecting the performance.

[0079] In this application, Dv10 and Dv99 of the positive electrode active material can be measured by using a laser particle size analyzer (such as Malvern Master Size 3000) with reference to the standard GB / T19077.1-2016. The physical definitions of Dv10 and Dv99 are as follows:

[0080] Dv10: the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 10%;

[0081] Dv99: The particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 99%.

[0082] In some embodiments, y and a satisfy the following relationship: (π×y 2 The value of ) / (10000×a) is 0.01 to 115, preferably 0.01 to 20, and further preferably 0.01 to 10.

[0083] In some embodiments, the Dv10 of the positive electrode active material is 3 μm to 10 μm, preferably 3.2 μm to 8 μm.

[0084] In some embodiments, the positive electrode active material Dv10 / Dv99 is z, z ranges from 0.01 to 0.5, preferably 0.05 to 0.4; a / z is 0.01 to 1, preferably 0.05 to 0.3.

[0085] In some embodiments, the positive electrode active material includes lithium manganese oxide LiMn2O4, optionally lithium nickel cobalt manganese oxide Li x Ni m Co n Mn p O2, where 0.95≤x≤1.05, 0.98≤m+n+p≤1.02, and where 0≤m<1, 0≤n<1, 0<p≤1 (e.g. LiNi 0.8 Co 0.1 Mn 0.1 O2), and optionally LiFeO4.

[0086] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector, for example, as a metal foil, an aluminum foil may be used; as a composite current collector, it may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, polyethylene (PE), etc.).

[0087] In some embodiments, the positive electrode film layer further includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0088] In some embodiments, the content of the binder in the positive electrode film layer may be 0.1 wt % to 6 wt %, optionally 0.5 wt % to 5 wt %, and preferably 0.8 wt % to 3 wt %, based on the total weight of the positive electrode film layer.

[0089] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, carbon nanotubes, graphene, and carbon nanofibers.

[0090] In some embodiments, the content of the conductive agent in the positive electrode film layer may be 0.1 to 6 weight %, optionally 0.5 to 5 weight %, and preferably 0.8 to 3 weight %, based on the total weight of the positive electrode film layer.

[0091] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0092] negative electrode

[0093] In the present application, the negative electrode is a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0094] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0095] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, polyethylene (PE), etc.).

[0096] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0097] In some embodiments, the weight fraction of the negative electrode active material in the negative electrode film layer is not less than 80%, optionally not less than 90%, and more preferably not less than 95%. In some embodiments, the negative electrode film layer may also optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0098] In some embodiments, the weight fraction of the binder in the negative electrode film layer may be 0.1% to 6% by weight, and may be optionally 0.5 to 5% by weight.

[0099] In some embodiments, the negative electrode film layer may further include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0100] In some embodiments, the weight fraction of the conductive agent in the negative electrode film layer may be 0.1% to 6% by weight, and may be optionally 0.5 to 5% by weight.

[0101] In some embodiments, the negative electrode film layer may further optionally include other additives, such as a thickener (eg, carboxymethyl cellulose (CMC)).

[0102] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0103] Isolation film

[0104] In the present application, there is no particular restriction on the type of the isolation membrane, and any known isolation membrane with good chemical stability and mechanical stability can be selected. The material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular restriction.

[0105] In the present application, the positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a winding process or a lamination process.

[0106] In the present application, the lithium metal battery may include an outer packaging, which can be used to encapsulate the electrode assembly and the electrolyte.

[0107] In the present application, the outer packaging of the lithium metal battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium metal battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0108] In the present application, there is no particular limitation on the shape of the lithium metal battery, which may be cylindrical, square or any other shape.

[0109] Another aspect of the present application provides an electrical appliance comprising the electrochemical device.

[0110] Example

[0111] The following describes the implementation of the present application through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application.

[0112] The lithium-ion battery preparation process is as follows:

[0113] (1) Preparation of positive electrode sheet

[0114] The positive electrode active material (single positive electrode material or mixed positive electrode material), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72 weight %; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the coated aluminum foil is dried at 100° C., and then, after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74 mm×867 mm is obtained, and the pole ears are welded for standby use.

[0115] (2) Preparation of negative electrode sheet

[0116] The negative electrode active material artificial graphite, the conductive agent Super P, the thickener sodium carboxymethyl cellulose (CMC-Na) and the binder styrene-butadiene rubber (SBR) are mixed in a weight ratio of 96:2:0.8:1.2, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 54 weight %; the negative electrode slurry is uniformly coated on the negative electrode current collector copper foil; the coated copper foil is dried at 85°C, and then after cold pressing, cutting and slitting, a negative electrode sheet with a specification of 79 mm×872 mm is obtained, and the pole ears are welded for standby use.

[0117] (3) Preparation of electrolyte

[0118] In a dry argon atmosphere glove box, the solvent is mixed in a ratio of ethylene carbonate (EC): diethyl carbonate (DEC): ethyl methyl carbonate (EMC) = 3:5:2 (mass ratio), and then lithium hexafluorophosphate (12.5% ​​by weight, based on the mass of the basic electrolyte) is added to obtain a basic electrolyte. According to the type and mass content recorded in the following table, the corresponding additives are added to the basic electrolyte, dissolved and fully stirred to obtain an electrolyte. Among them, the additive content recorded in each table is based on the mass of the electrolyte.

[0119] (4) Preparation of isolation membrane

[0120] A 9 μm thick polyethylene (PE) substrate layer was selected, and polyvinylidene fluoride (PVDF) slurry and inorganic particles (the ratio of flaky boehmite and Al2O3 was 70:30) slurry were coated on one side of the polyethylene substrate layer. After drying, the final isolation membrane was obtained. The coating thickness was 3 μm and the porosity of the isolation membrane was 55%.

[0121] (5) Preparation of lithium-ion batteries

[0122] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; after welding the pole ears, the electrode assembly is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried electrode assembly, and after vacuum packaging, standing, formation (0.02C constant current charging to 3.3V, and then 0.1C constant current charging to 3.6V), shaping, capacity testing (0.5C constant current and constant voltage charging to 4.2V, 0.5C discharge to 3.0V) and other processes, a soft-pack lithium-ion battery is obtained.

[0123] It should be noted that in the following Example 1-1, the positive electrode active material is composed of 90% by mass of LiMn2O4 and 10% by mass of LiNi 0.8 Co 0.1 Mn 0.1 The positive electrode active material has a Dv99 of 45 μm and a Dv10 of 10 μm.

[0124] Unless otherwise specified, in Table 1, the batteries in Example 1-1 and other examples are prepared by substantially the same method, and the only difference between them is that the content of FEC and the relevant parameters of the positive electrode active material recorded in Table 1 are adjusted. Similarly, in Table 2, the preparation method of the batteries in Examples 2-1 to 2-10 is substantially the same as that in Example 1-4, except that different contents of FEC and different positive electrode active materials and particle sizes are used. Here, it can be understood that materials with different Dv99 and Dv10 can be obtained by adjusting the sintering temperature and time of the preparation process, and the Mn element content can be fine-tuned by element doping as needed. In Table 3, the preparation method of the batteries in Examples 3-1 to 3-8 is substantially the same as that in Example 1-4, except that different contents of FEC are used and different contents of vinylene carbonate are added. In Table 4, the preparation method of the batteries in Examples 4-1 to 4-15 is substantially the same as that in Example 1-4, except that different types and contents of additives are added. In Table 5, the preparation methods of the batteries in Examples 5-1 to 5-4 are substantially the same as that of Example 1-4, except that different contents of dimethyl carbonate are added.

[0125] Performance Test:

[0126] Cyclic Testing and Cyclic Thickness Change

[0127] The battery cell is placed in a 45℃ high temperature box, charged to 4.2V at 0.5C cross current constant voltage, the thickness is measured as h1, and it is left to stand for 15 minutes. Then it is discharged to 3.0V at 0.5C cross current and left to stand for 15 minutes as one cycle. The capacity of the first cycle is recorded as C1, the cycle is 100 times, and the discharge capacity of the 100th cycle is recorded as C 100, thickness is h 100 , then the cycle capacity retention rate is [C 100 / C1]×100%, thickness change rate [(h 100 / h1)-1]×100%

[0128] Low temperature discharge test

[0129] Place the battery in a high and low temperature box, adjust the temperature to 25°C, then charge it to 4.2V at 0.2C constant current and constant voltage, then discharge it to 3.0V at 0.2C, and record the discharge capacity at this time as C 25 (mAh); then charge to 4.2V at 0.2C constant current and constant voltage, then adjust the temperature of the high and low temperature box to -20℃, and then discharge to 3.0V at 0.2C cross current, record the discharge capacity at this time as C -20 (mAh), low temperature discharge capacity retention rate [C -20 / C 25 ]×100%

[0130] High temperature full charge storage

[0131] First, the battery cell is charged to 4.35V at 0.5C constant current and constant voltage at 25℃, and then discharged to 3.0V at 0.2C (discharge capacity is recorded as C0), and then charged to 4.35V at 0.5C constant current and constant voltage, and the initial thickness d1 is tested. Then the battery cell is placed in a 60℃ high temperature furnace and stored for 30 days before the thickness d2 is tested. After the storage, the battery cell is discharged to 3.0V at 0.2C at 25℃, and then charged to 4.35V at 0.5C constant current and constant voltage, and then discharged to 3.0V at 0.2C (discharge capacity is recorded as C 30 ).

[0132] The thickness change rate of high temperature full charge storage is: [(d2 / d1)-1]×100%.

[0133] The recoverable capacity after storage at 60℃ for 30 days is: [(C0 / C 30 )-1]×100%.

[0134] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Tables 1 to 5.

[0135] Table 1 Effect of fluoroethylene carbonate (FEC) content and unit reaction area (c) of positive electrode active material on cycle and storage performance

[0136]

[0137]

[0138] As can be seen from Examples 1-1 to 1-12 and Comparative Examples 1-1 and 1-2 in Table 1, the ratio of the content of fluoroethylene carbonate in the cathode material to the unit reaction area c of the cathode active material can improve both the battery cycle and high-temperature storage performance within a certain range. This is mainly because fluoroethylene carbonate can undergo oxidative decomposition on the cathode surface to form a protective layer with the lithium salt in the electrolyte on the cathode surface. Based on the appropriate unit reaction area of the cathode active material, an appropriate content of FEC can protect the cathode active material while reducing the adverse effects of HF generated by the decomposition of FEC on the cathode, and at the same time improve the stability of the anode interface during cycling and storage.

[0139] Table 2 Effects of Different Cathode Active Materials and Their Particle Sizes on Cycling Performance and Low-Temperature Discharge Performance

[0140]

[0141] Table 2 shows the Dv10, Dv99, cycling performance, and low-temperature discharge performance data corresponding to different lithium manganate materials and mixed materials. Among them, when the value of a / z is from 0.01 to 1, the electrochemical device can maintain better comprehensive performance. In particular, when the value of a / z is from 0.05 to 0.3, the discharge capacity retention rate of the electrochemical device under low-temperature conditions is significantly improved. This may be because when a / z is maintained within an appropriate range, there will be no local side reaction phenomenon caused by the particle size distribution, and the interface between the cathode active material and the electrolyte has overall consistency, which has a relatively positive impact on the ion transport performance.

[0142] Table 3 Effects of the Addition of Vinylene Carbonate (VC) on Cycling Performance

[0143]

[0144] As can be seen from Examples 3-1 to 3-8 in Table 3, the addition of VC can further improve the cycling capacity retention rate and reduce the thickness change during cycling. In particular, when the contents of VC and FEC satisfy 0.11a - 0.05% < b < 5.1a + 0.45%, while the cycling retention rate of the electrochemical device is further improved, the high-temperature thickness expansion is significantly improved. This may be because VC and FEC copolymerize to form an organic polymer component. When 0.11a - 0.05% < b < 5.1a + 0.45% is satisfied, the stability of the SEI is improved, reducing the degree of damage to the SEI by the reduction on the anode and the thickness increase caused by side reactions. 2+ The reduction on the anode reduces the degree of damage to the SEI and the thickness increase caused by side reactions.

[0145] Table 4 Effects of Various Additives on Storage Performance

[0146]

[0147]

[0148] Table 4 shows the effect of adding additive A on storage stability. On the one hand, it can improve gas production during high-temperature storage, and on the other hand, it can improve capacity recovery after storage. This is mainly because the combination of this type of additive with FEC can reduce the side reactions of the system under high-temperature storage conditions and reduce the consumption of active lithium by the electrolyte under long-term storage. In particular, when LiFSI and at least one of LiPO2F2 and 2-PY are further added to the electrolyte, the overall performance of the electrochemical device is significantly improved.

[0149] Table 5 Effect of adding dimethyl carbonate (DMC) on cycle performance and storage performance

[0150]

[0151] In Table 5, it can be seen from Examples 5-1 to 5-4 and Example 1-4 that adding a certain amount of DMC can improve the cycle and storage performance. This is mainly because the presence of a small amount of DMC can inhibit the decomposition of EMC and reduce the deterioration of the cycle life caused by side reactions; however, when the DMC content is too high, storage gas production and cycle attenuation may occur due to the insufficient oxidation resistance of DMC.

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5%, based on the mass of the electrolyte; The electrolyte further comprises vinylene carbonate, and the content b of the vinylene carbonate is 0.01% to 5%, based on the mass of the electrolyte; The positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and a content of the Mn element is greater than or equal to 15%, based on the mass of the positive electrode active material; The unit reaction area of ​​the positive electrode active material is c, expressed in m 2 / cm 2 a and c satisfy the following relationship: 0.0006≤a / c≤6.25; wherein the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material.

2. The electrochemical device according to claim 1, which satisfies at least one of the following conditions: a) 0.0006≤a / c≤2.5; b) the content of the fluoroethylene carbonate is 0.05% to 5%, based on the mass of the electrolyte; c) The range of W is 8 mg / cm 2 Up to 35mg / cm 2 , the range of BET is 1m 2 / g to 5m 2 / g. 3 . The electrochemical device according to claim 1 , wherein the Dv10 / Dv99 of the positive electrode active material is z, and a / z is 0.01 to 1.

4. The electrochemical device according to claim 1, wherein at least one of the following conditions is satisfied: a) 0.11a-0.05% <b<5.1a+0.45%; b) In the positive electrode active material, the content of manganese element is x, satisfying b / x≥10 -3 .

5. The electrochemical device according to claim 1 or 2, wherein the electrolyte further comprises an additive A, the additive A being selected from at least one of methylene disulfonate, 1,3-propylene sultone, 1,3-propane sultone, succinic anhydride, lithium difluorophosphate, 2-fluoropyridine and lithium bis(fluorosulfonyl)imide, and the content of the additive A is 0.01 to 10%, based on the mass of the electrolyte.

6. The electrochemical device according to claim 1 or 2, wherein the electrolyte further comprises dimethyl carbonate, and the content of dimethyl carbonate is less than or equal to 5%, based on the mass of the electrolyte.

7. The electrochemical device according to claim 1 or 2, wherein the positive electrode active material comprises at least one of lithium manganese oxide and lithium nickel cobalt manganese oxide.

8. The electrochemical device according to claim 1 or 2, which satisfies at least one of the following conditions: a) the content of the fluoroethylene carbonate is 0.05% to 3%, based on the mass of the electrolyte; b) The range of W is 13 mg / cm 2 Up to 30mg / cm 2 , the range of BET is 1.2m 2 / g to 3.5m 2 / g; c) the electrolyte further comprises vinylene carbonate, the content of the vinylene carbonate being 0.01% to 2%, based on the mass of the electrolyte; d) the electrolyte further comprises dimethyl carbonate, the content of the dimethyl carbonate being less than or equal to 1%, based on the mass of the electrolyte; e) the content of Mn element in the positive electrode active material is less than or equal to 60%; f) The Dv10 / Dv99 of the positive electrode active material is z, and a / z is 0.05 to 0.

3.

9. An electrical appliance comprising the electrochemical device according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Electrochemical device and electronic device including same

    CN113013480A

  • Electrochemical device and electronic equipment comprising same

    CN113206295A

  • Lithium Secondary Battery

    US20250118743A1